A formação do cidadão no ensino público fundamental entre as décadas de 70 e 90: considerações sobre a legislação educacional - Tibola, Luciana Rosniak (2006)
The current education legislation is highlighted, among other aspects, by the importance given to the student s preparation to the exercise of citizenship , reflecting an image of an ideal citizen, whose materialization becomes questionable before the school reality. Before it is applied or reformulated by the school, this concept needs to be understood. In order to do this it becomes relevant to seek for elements in the preceding legislations, which can contribute to the comprehension of the concept of citizenship, proposed to be worked by schools and the context of their production. Such elements can be found in the recent history of the Brazilian education, more precisely in the 70s, 80s and 90s. The methodology applied consists of bibliographical and documental research, applying the content analysis to describe and interpret the documents and the bibliography used. This work, which is linked to the Line of Research in Education, Politics and Culture, has revealed that, the citizen proposed by the education legislations in the studied periods, was defined by economical aspects, that is, for the work relations and for the position occupied by Brazil in the world economic market. The political aspect of citizenship has been used to illustrate the official speech. It was also clear the attribution of a salvation role to the school before the society problems. However, in spite of pointing the school as an answer to the national problems, there is a great distance between the expectations laid out in the school and the educational politics effectively applied.